PENGARUH PERAWATAN METODE KANGURU/KANGAROO MOTHER CARE TERHADAP STABILITAS SUHU TUBUH BAYI BERAT LAHIR RENDAH DI RUANG PERISTI RSUD KEBUMEN - Sri Abdi Lestari; Cahyu Septiwi; Ning Iswati (LPPM UNIVERSITAS MUHAMMADIYAH GOMBONG, 2014)
low birthweight Infants is a major cause of morbidity and mortality inneonates. Diseases that occur to low birth weight infants are usuallyassociated with immaturity of organ function resulting in the instability ofbody temperature. One of the effective treatments for temperatureinstability is skin contact with the skin care/ skin to skin by using with thekangaroo mother care. It is a method of treatment of the newborn by putting thebaby in the mother's chest (skin to skin) to channel the warmth to thebaby. This study aim is todetermine the influence of kangaroo mother care treatment for the temperaturestability of low birth weight infants in Peristi Ward KebumenHospital. This study used quasi-experimental analysis using frequencydistributions and bivariate analysis using chi square statistic test. allrespondents (100%) in the intervention group had normal bodytemperature. 32.5% respondents in the control group had abnormal bodytemperature. There are influences of kangaroo mother care for the baby'sbody temperature stability with p: 0.000. Keywords:kangaroo mother care, temperature stability, low birth weight infants